Exploring the metaverse: Opportunities for business development and creative industries in education - Saheed Oluwaseun Lawal; Tajudeen Ade Jamiu (Himpunan Pengembang Kurikulum Indonesia, 2025)
The rapid technological advancements have led to a profound digital transformation, with the metaverse emerging as one of the most disruptive innovations in education and creative industries. This study aims to explore the opportunities and challenges faced by entrepreneurs in the education and creative sectors in leveraging the metaverse as a space for innovation and value creation. Using a mixed-method design (quantitative and qualitative), the research collects data through online surveys and in-depth interviews with entrepreneurs and industry experts. Findings from the survey show that the majority of entrepreneurs in the gaming, retail, and education sectors are using the metaverse to expand market reach, reduce financial risks, and enhance international collaboration. However, technical challenges such as platform interoperability issues and ethical concerns related to privacy and content moderation remain significant barriers. The study identifies the need for clear legal and ethical frameworks to support sustainable growth in the metaverse. Based on these findings, further research is recommended to develop clear ethical guidelines and solutions for technical challenges, as well as to monitor the long-term development of metaverse use in business and education. Abstrak Perkembangan teknologi yang pesat telah mengarah pada transformasi digital yang mendalam, dengan metaverse sebagai salah satu inovasi paling disruptif dalam dunia pendidikan dan industri kreatif. Penelitian ini bertujuan untuk mengeksplorasi peluang dan tantangan yang dihadapi oleh pengusaha di industri pendidikan dan kreatif dalam memanfaatkan metaverse sebagai ruang untuk inovasi dan penciptaan nilai. Dengan menggunakan desain metode campuran (kuantitatif dan kualitatif), penelitian ini mengumpulkan data melalui survei online dan wawancara mendalam dengan pengusaha dan pakar industri. Temuan dari survei menunjukkan bahwa mayoritas pengusaha di sektor game, ritel, dan pendidikan memanfaatkan metaverse untuk memperluas jangkauan pasar, mengurangi risiko finansial, dan meningkatkan kolaborasi internasional. Namun, tantangan teknis seperti masalah interoperabilitas platform dan masalah etika terkait privasi dan moderasi konten tetap menjadi hambatan signifikan. Penelitian ini mengidentifikasi perlunya kerangka kerja hukum dan etika yang jelas untuk mendukung pertumbuhan yang berkelanjutan dalam metaverse. Berdasarkan temuan ini, disarankan agar penelitian lebih lanjut dilakukan untuk mengembangkan pedoman etika yang jelas dan solusi untuk tantangan teknis, serta memantau perkembangan jangka panjang dari penggunaan metaverse di dunia bisnis dan pendidikan. Kata Kunci: Inovasi bisnis; kolaborasi internasional; metaverse; pendidikan digital